Task Demand Changes Motor Control Strategies in Vertical Jumping - Cushion, Emily J; Warmenhoven, John; North, Jamie S; Cleather, Daniel J (Journal of motor behavior, 2021)
The purpose of this study was to examine the motor control strategies employed to control the degrees of freedom when performing a lower limb task with constraints applied at the hip, knee, and ankle. Thirty-five individuals performed vertical jumping tasks: hip flexed, no knee bend, and plantar flexed. Joint moment data from the hip, knee, and ankle were analyzed using principal component analysis (PCA). In all PCA performed, a minimum of two and maximum of six principal components (PC) were required to describe the movements. Similar reductions in dimensionality were observed in the hip flexed and no knee bend conditions (3PCs), compared to the plantar flexed condition (5PCs). A proximal to distal reduction in variability was observed for the hip flexed and no knee bend conditions but not for the plantar flexed condition. Collectively, the results suggest a reduction in the dimensionality of the movement occurs despite the constraints imposed within each condition and would suggest that dimensionality reduction and motor control strategies are a function of the task demands.
Keywords: koleno; degrees of freedom; biomechanika; Biomechanical Phenomena; Knee; constraints; proximal to distal pattern; vertical jumping; Humans; kolenní kloub; pohyb; Ankle; principal component analysis; kotník; Knee Joint; lidé; Movement